Perbenihan Sayuran di Indonesia: Kondisi Terkini dan Prospek Bisnis Benih Sayuran - Aswaldi Anwar; , Sudarsono; Satriyas Ilyas (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2005)
Indonesian Vegetable Seeds: Current Condition and Prospects in Business of Vegetable Seeds